Correlation of meteorological parameters with sorghum grain mold incidence - and B.P. KURUNDKAR, SUNITA J. MAGAR (Indian Phytopathology, 2005)
Environmental parameters were correlated with incidence and intensity of grain mold and occurrence of different mold flora on twelve promising sorghum genotypes. These correlations were worked out from 50 percent flowering to crop harvest and from 7 and 15 days before harvesting till harvesting. Results indicated that significant and positive correlation existed between mean temperature, relative humidity, bright sunshine hours and wind speed for incidence and intensity of grain mold when these parameters were considered from 50% flowering to crop harvest. When meteorological parameters considered one and two weeks before harvesting, rainfall and humidity (a.m.) positively and significantly correlated with intensity of grain mold in field.